Unleashing the full power of LHCb to probe stealth new physics. (1st February 2022) - Borsato, M; Cid Vidal, X; Tsai, Y; Vázquez Sierra, C; Zurita, J; Alonso-Álvarez, G; Boyarsky, A; Brea Rodríguez, A; Buarque Franzosi, D; Cacciapaglia, G; Casais Vidal, A; Du, M; et al.
Abstract: In this paper, we describe the potential of the LHCb experiment to detect stealth physics. This refers to dynamics beyond the standard model that would elude searches that focus on energetic objects or precision measurements of known processes. Stealth signatures include long-lived particles and light resonances that are produced very rarely or together with overwhelming backgrounds. We will discuss why LHCb is equipped to discover this kind of physics at the Large Hadron Collider and provide examples of well-motivated theoretical models that can be probed with great detail at the experiment.